Modernism, environmental assessment and the sustainability argument : moving towards a new approach to project-based decision-making in South Africa - Audouin, Michelle (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DPhil (Philosophy))--University of Stellenbosch, 2009.